Nairobi in the making landscapes of time and urban belonging - Smith, Constance ca. 20./21. Jh (Eastern African series, 2019)
Examines the making and remaking of Nairobi, one of Africa's most fragmented, vibrant cities, contributing to debates on urban anthropology, the politics of the past and postcolonial materialities